Physiological Importance of food intake on Niyat Kaal w.s.r. to Digestive Disorders - Singh, Sangeeta; Sharma, Rajesh Kumar; Sharma, Dinesh Chandra (International Research Journal of Ayurveda & Yoga, 2021)
In Ayurveda the Ahara (diet) and Anna (food) are the two major factors that are the means of healthy lifestyle and wellness. Healthy and wholesome food always nourishes the body, mind and soul while the unhealthy and unwholesome diet leads to the development of disease or unhealthy state of an individual. According to the Ayurveda although the digestive capacity or the Jathargni is different for each person but the quality and appropriate quantity of food is necessary along with the food intake on adequate time for the healthy lifestyle. Acharya Charaka mention the importance of Kaal Bhojan i.e, the proper time of food intake by saying that food intake at adequate time leads to healthy state of a person. Ayurveda emphasis more on the time of the intake of food. even if the food is taken in proper quantity and is of proper quality the time and the interval at which the food is taken is necessary for the proper digestion of food. If the food is taken at inadequate time it can leads to various digestive disorders. This article presents the importance of food intake on the Niyat kaal or on adequate time, its physiological importance and digestive disorders which can happen to our body if we do not take food on adequate time.